The association between stress and high-fat intake with hypertension among pregnant women in Bondowoso Regency - Amalina Hilyatu Sholihah; Adistha Eka Noveyani; Abdul Azis Akbar (AcTion: Aceh Nutrition Journal, 2025)
Hypertension affects approximately 10% of pregnancies globally and remains a leading cause of maternal mortality and morbidity. Mothers with hypertension in their first pregnancy are at an elevated risk for preeclampsia in subsequent pregnancies.  This study aimed to analyze the relationship between stress and high-fat intake and the incidence of hypertension in pregnant women. This was an observational study that used a cross-sectional approach from May to June 2024. The study population included pregnant women who were patients of the Maesan Health Center and residing in Bondowoso Regency. The sample selection used Slovin's formula: 73 out of 263 pregnant women. Stress variables were measured using the Revised Prenatal Distress Questionnaire (NuPDQ), a 2 × 24-hour recall questionnaire for fat intake measurements, and blood pressure measurements using a tensimeter. Univariate analysis described each variable, including respondents' stress status and high-fat dietary intake. Moreover, bivariate analysis used chi-square tests to assess the relationship between the independent variables (stress and fat intake) and the dependent variable (hypertension). This study found that there was an association between stress and high-fat intake and the incidence of hypertension, with p-values <0,001 and <0,001, respectively.  We recommend addressing both stress management and dietary habits as crucial in prenatal care programmes.